Uso do Big Data na construção de valor no varejo: estudo de caso do Walmart - Prates, Mariana Lima (2016)
Several changes in access to information have led the consumer to a new level; consumers today are more accessible to receive, search and disseminate information at anytime and anywhere. Innovative retailers had accepted this condition and started interacting with their customers in their environment. These interactions generate, uninterruptedly, an infinite mass of data known as Big Data. This study is an analysis of the worldwide retail activities in order to verify how the use of Big Data can contribute to the construction of customer value, focused on the American retailer Walmart. Through a case study, it was possible to identify how innovative and technologyfocused positioning in information analysis has brought benefits to the company, creating customer value and exceeding its expectations. Among the results found in the US operation there are the growth of purchases made online with the option to pick up in a physical store and in the number of customers that choose the use of geolocation in order to speed up the purchase process and, in Brazil there are reduction in the number of complaints, growth of interactions with customers in social networks and increased sales online